2011
DOI: 10.1016/j.cell.2011.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing of Ion Channel Genes Reveals Complex Profiles Confounding Personal Risk Assessment in Epilepsy

Abstract: Ion channel mutations are an important cause of rare Mendelian disorders affecting brain, heart, and other tissues. We performed parallel exome sequencing of 237 channel genes in a well characterized human sample, comparing variant profiles of unaffected individuals to those with the most common neuronal excitability disorder, sporadic idiopathic epilepsy. Rare missense variation in known Mendelian disease genes is prevalent in both groups at similar complexity, revealing that even deleterious ion channel muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
288
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(310 citation statements)
references
References 75 publications
21
288
0
1
Order By: Relevance
“…In fact, the observation of deleterious mutations in 237 ion-channel genes with the same prevalence in individuals with epilepsy and control subjects suggested that, at least for these genes, the personal risk assessment in epilepsy depends more on the combination of the variants rather than specific deleterious variants. 41 The lack of enrichment of protein-disrupting ion-channel mutations in individuals with epilepsy has been confirmed by Heinzen et al 42 These authors also demonstrated that single epilepsy-susceptibile variants identified by exome sequencing in patients with idiopathic generalized epilepsy (juvenile myoclonic epilepsy and absence epilepsy), although rare, were possibly real risk factors, each of them accounting for only a small fraction of individuals with epilepsy. This burden of data makes evident the complex architecture of epilepsy with genetic heterogeneity much higher than expected.…”
Section: Discussionmentioning
confidence: 61%
“…In fact, the observation of deleterious mutations in 237 ion-channel genes with the same prevalence in individuals with epilepsy and control subjects suggested that, at least for these genes, the personal risk assessment in epilepsy depends more on the combination of the variants rather than specific deleterious variants. 41 The lack of enrichment of protein-disrupting ion-channel mutations in individuals with epilepsy has been confirmed by Heinzen et al 42 These authors also demonstrated that single epilepsy-susceptibile variants identified by exome sequencing in patients with idiopathic generalized epilepsy (juvenile myoclonic epilepsy and absence epilepsy), although rare, were possibly real risk factors, each of them accounting for only a small fraction of individuals with epilepsy. This burden of data makes evident the complex architecture of epilepsy with genetic heterogeneity much higher than expected.…”
Section: Discussionmentioning
confidence: 61%
“…The variation within each group appears as great as the difference between groups. Variation between patients with identical mutations may be accounted for by differences in genetic background, including genetic variation in other channel genes,39 as well as stochastic variation during the development of the nervous system. The course of drug treatment itself may influence clinical outcome 5…”
Section: Discussionmentioning
confidence: 99%
“…48,49 This concept has also been proposed in a recent work studying genetic complexity in sporadic idiopathic epilepsy, suggesting that oligogenic electrical relationship may likely have a role even in 'monogenic' channelopathies, as carriers of such mutations often show a spectrum of clinical phenotypes, including the absence of disease, even within the same pedigree. 50 Indeed, in our cohort 5 out of 7 individuals carrying Z3 risk genotypes had experienced MAE, while only 1 out of 29 patients not carrying any risk genotype suffered life-threatening arrhythmias. This observation corroborates the association between at-risk genotypes and severe phenotype and underline the possibility that the contemporary presence of these alleles may have a cumulative effect on the phenotype.…”
Section: Discussionmentioning
confidence: 99%